Educating The Heart: The Concept of Qalb Education in Minhāju Al-Atqiyā’i fi Syarḥi Ma’rifati Al-Ażkiyā’i ilā Ṭarīqi Al-Auliyā’i by KH. Sholeh Darat - M Rikza Chamami; Abdurrahman Mas’ud; Ruswan Ruswan (FITK UIN Walisongo, 2021)
Qalb education (heart education) becomes one of the keys to cultivating and nurturing human characters. The focus of this research is to examine the concept of heart education from the perspective of KH. Sholeh Darat (1820-1903), the role of the heart in education, and the function of heart health in cultivating humans' characters. This research uses library research methods focusing on KH. Sholeh Darat’s Minhāju Al-Atqiyā'i fī Syarḥi Ma’rifati Al-Ażkiyā'i ilā Ṭarīqi Al-Auliyā'i using hermeneutic and historical approaches. The study found that the concept of heart education from KH. Sholeh Darat's perspective eliminates ignorance and seeks knowledge to make humans appreciate the understanding and implement it. Heart education is centered on two main things: mulāzamati al-Zikri (continuous dhikr) and mulāzamati tilāwati kitābullāh (continuous reading of the Qur'an). In addition, the physical transformation of education needs to be supported with humans' healthy and pure hearts. Heart therapies to support heart education include reading the Qur'an, emptying one's stomach, night prayers, tadharru' (pleading) at suhoor time, and mujālasah (gathering) with pious people. Lastly, noble teachers can accomplish heart education with perfect guidance (tarbiyatu al-shaykh al-mursyīd al-kāmil).